2020
DOI: 10.1002/pep2.24208
|View full text |Cite
|
Sign up to set email alerts
|

Self‐assembly of hairpin peptides mediated by Cu(II) ion: Effect of amino acid sequence

Abstract: The alteration of amino acid register in peptides could affect their folding properties and thus functions. The effect of sequence in metal ion induced folding of peptide/ protein is important in the design of new functional protein structures, such as biomimetics. In this paper, a set of hairpin peptides with identical composition but different histidine locations have been designed to exploit the metal ion-mediated peptide intramolecular folding transformation through the adjustment of histidine and lysine r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…This may be due to stable species formation at this ratio of Cu 2+ which is supported by the presence of a 2 : 1 C 14 -FH(Trt)-OH : Cu complex species found through mass spectrometry as stated earlier. Based on these spectroscopic results suggesting involvement of the amide backbone and literature, 54,57–60 potential structures have been hypothesized and shown in Fig. 8 demonstrating a metal ion binding pocket potentially formed by the imidazole and amide backbone in addition to free aromatic rings to allow for self-assembly through π-interactions into supramolecular nanostructures.…”
Section: Resultsmentioning
confidence: 92%
“…This may be due to stable species formation at this ratio of Cu 2+ which is supported by the presence of a 2 : 1 C 14 -FH(Trt)-OH : Cu complex species found through mass spectrometry as stated earlier. Based on these spectroscopic results suggesting involvement of the amide backbone and literature, 54,57–60 potential structures have been hypothesized and shown in Fig. 8 demonstrating a metal ion binding pocket potentially formed by the imidazole and amide backbone in addition to free aromatic rings to allow for self-assembly through π-interactions into supramolecular nanostructures.…”
Section: Resultsmentioning
confidence: 92%
“…Because basic amino acid residues (histidines and lysines) in the molecule were protonated and positively charged at pH 4.0, CBHH could not fold intramolecularly due to the electrostatic repulsion. 22,27,28 In our previous studies, we showed that Cu(II) and Pt(IV) could induce the intramolecular folding and self-assembly of CBHH, and we also fabricated CuS and Pt nanomaterials under the regulation of CBHH. In the present study, we found that the addition of dicarboxylates promoted the β-sheet formation.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Another example of de novo designed β-hairpin peptide assembly was demonstrated by Xu and co-workers, in which Cu(II) coordination with the designed peptide having the βturn V D PPT sequence along with lysine and histidine residues showed concentration and pH dependent β-sheet nanofibrillar formation. 190 Nowick and co-workers, who have used a macrocyclic β-sheet forming peptide sequence consisting of two β-strands derived from Aβ 16−22 connected by two ornithine turn units to construct supramolecular double walled nanotubes. 189 They showed using extensive X-ray crystallography that the inner wall was composed of a network of hydrogen-bonded dimers and the outer wall comprised of a network of β barrel-like tetramers (Figure 12).…”
Section: Peptide Synthesismentioning
confidence: 99%